THE DEVELOPMENT STRATEGY OF SIMBAT AGRO TOURISM IN JEMBER REGENCY - pipit nani pratiwi; Hari Rujito; Bagus Putu Yudhia K (Universitas Muhammadiyah Jember, 2019)
The potential possessed by SIMBAT Agro Tourism is huge, the land is wide enough with a land area of around 7 hectares, the charm of attractive mountain nature attractions such as tourist spots in Batu city with access close to the Jember city area, the community environment is very supportive, and human resources enough available to make this Agrotourism very potential to be developed. But behind the great potential of SIMBAT Agrotourism, its development is still not optimal. Seeing the potential and various benefits of the development of SIMBAT Agro-tourism, as well as seeing the condition of agro-tourism that still has not made the main strategic priorities that must be done, and the Agro-tourism design has not been made in accordance with the needs and desires of tourists. Therefore the purpose of this study is to find a strategy towards the development of SIMBAT agro-tourism in Jember Regency. The analytical methods used in this study are IFE, EFE, IE, SWOT, QSPM, and QFD. The results of the study based on QSPM analysis the priority strategy is Optimizing excellence by improving the quality of service to consumers. The QFD analysis obtained attributes of tourist needs that become the top priority seen from the level of importance is cleanliness and beauty of the tourist environment, while the service attribute which is the top priority seen from the level of importance